Penerapan Model PBL dalam Mengembangkan Kemampuan Berpikir Kritis dan Minat Belajar Pendidikan Pancasila - Fajriatus Arfani; Muhamad Azril Gibran; Nur Indah Wahyuni; Marno M (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The background to this research is the use of conventional learning models by class V teachers at SDN 05 Krajankulon which makes students bored and unable to optimize the learning process. Therefore, the aim of this research is to develop and improve students' critical thinking skills and interest in learning, especially in learning Pancasila Education subjects. This type of research is descriptive qualitative with the research subjects being all 25 class V students at SDN 05 Krajankulon. The steps of this research are (1) planning, (2) interviews, (3) observation, and (4) documentation. The results of the research show that providing learning assistance using the problem based learning model assisted by PowerPoint can improve students' critical thinking skills and interest in learning which can be seen in the process of implementing the problem based learning syntax. Students are very enthusiastic about the learning provided as shown by their willingness to express opinions and abilities. summarizing the information or ideas presented, as well as the results of learning evaluations that have previously been prepared using HOTS indicators or at cognitive level C4-C5 with an average score before providing learning assistance of 71.6 to 85.